2018
DOI: 10.1093/ntr/nty165
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Feasibility Study of a Hybrid Telephone Counseling/Text Messaging Intervention for Post-Discharge Cessation Support Among Hospitalized Smokers in Brazil

Abstract: This study extends research on hospital-initiated smoking cessation by establishing the feasibility of a novel text-messaging approach for post-discharge follow up. Text messaging is a low-cost alternative to proactive telephone counseling that could help overcome resource barriers in middle and lower income countries. This hybrid texting/counseling intervention identified smokers in hospitals, established rapport through a single telephone follow-up, and expanded acceptability and reach of later support by us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(55 citation statements)
references
References 25 publications
0
45
0
8
Order By: Relevance
“…1). Twenty‐three studies [10,37–58] were RCTs (intervention n = 6593, control n = 5801). Three studies [59–61] were trials, but adopted a non‐randomized design (intervention n = 845, control n = 394).…”
Section: Resultsmentioning
confidence: 99%
“…1). Twenty‐three studies [10,37–58] were RCTs (intervention n = 6593, control n = 5801). Three studies [59–61] were trials, but adopted a non‐randomized design (intervention n = 845, control n = 394).…”
Section: Resultsmentioning
confidence: 99%
“…Cruvinel et al showed the feasibility of a hybrid telephone and text messaging counselling intervention among postdischarge hospitalised smokers in Brazil. 45 This hybrid intervention was well accepted by participants and resulted in noteworthy retention and cessation rates at 12 weeks.…”
Section: Discussionmentioning
confidence: 97%
“…Evidence suggests that the potential for text messages to deliver smoking cessation treatment may be even greater among hard-to-reach and socioeconomically disadvantage populations,44 like the one assessed in this study. Cruvinel et al showed the feasibility of a hybrid telephone and text messaging counselling intervention among postdischarge hospitalised smokers in Brazil 45. This hybrid intervention was well accepted by participants and resulted in noteworthy retention and cessation rates at 12 weeks.…”
Section: Discussionmentioning
confidence: 99%
“… 11 Among the remaining 14 studies, 8 showed no difference between the intervention and comparison groups. 12 - 19 Three studies included self-reported and biochemically tested abstinence and reported positive results based on self-reports but not on biochemical testing. 20 - 22 Two other studies reported positive results based on self-reports but did not include biochemical testing.…”
Section: Smoking Cessation Counselingmentioning
confidence: 99%